Lima Ekstrak Tumbuhan untuk Menekan Infeksi Bean common mosaic virus pada Tanaman Kacang Panjang - Lulu Kurnianingsih; Tri Asmira Damayanti (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Bean common mosaic virus (BCMV) is one of major virus infecting legumes and is difficult to manage. Utilization of plant extracts as systemic resistance inducer against virus is needed to study. The aim of the research is to evaluate the potency of five leaf extracts, i.e. from pagoda flower, spiny amaranth, four o’clock flower, Chenopodium amaranticolor, and herba andrographitis against BCMV. The effectiveness of leaf extracts were tested by spraying yard long bean leaves. Plants treated by spine spinach shown varied symptoms, while other treatments showed mild mosaic up to symptomless. The highest to lowest of disease incidence was showed by crude leaf extract of spine spinach (70%), four o’clock (10%), herba andrographitis (10%), while C. amaranticolor and pagoda are still uninfected. These results had positive correlation to disease severity and virus inhibition. Four of five tested leaf extracts, except spine spinach, showed their potency as systemic resistance inducer against BCMV. Key words: BCMV, plant extract, yard long bean